An overview of nuclear medicine research in the UK and the landscape for clinical adoption. Issue 12 (December 2021) - Young, Jennifer D.; Jauregui-Osoro, Maite; Wong, Wai-Lup; Cooper, Margaret S.; Cook, Gary; Barrington, Sally F.; Ma, Michelle T.; Blower, Philip J.; Aboagye, Eric O.
Abstract : Background and objectives: Nuclear medicine contributes greatly to the clinical management of patients and experimental medicine. This report aims to (1) outline the current landscape of nuclear medicine research in the UK, including current facilities and recent or ongoing clinical studies and (2) provide information about the available pathways for clinical adoption and NHS funding (commissioning) of radiopharmaceuticals. Methods: Evidence was obtained through database searches for UK-based nuclear medicine clinical studies and by conducting a questionnaire-based survey of UK radiopharmaceutical production facilities. A recent history of clinical commissioning, either through recommendations from the National Institute for Health and Care Excellence (NICE) or through NHS specialised services commissioning, was compiled from publicly available documents and policies. Results: The collected data highlighted the UK's active nuclear medicine research community and recent investment in new facilities and upgrades. All commissioning routes favour radiopharmaceuticals that have marketing authorisation and since 2017 there has been a requirement to demonstrate both clinical and cost-effectiveness. Whilst radiopharmaceuticals for molecular radiotherapy are well suited to these commissioning pathways, diagnostic radiotracers have not historically been assessed in this manner. Conclusions: We hope that by collating this information we will provide stimulus for future discussion and consensus statements around this topic. Abstract : Supplemental Digital Content is available in the text.